2020
DOI: 10.3390/rs12040694
|View full text |Cite
|
Sign up to set email alerts
|

A High-Resolution Global Map of Giant Kelp (Macrocystis pyrifera) Forests and Intertidal Green Algae (Ulvophyceae) with Sentinel-2 Imagery

Abstract: Giant kelp (Macrocystis pyrifera) is the most widely distributed kelp species on the planet, constituting one of the richest and most productive ecosystems on Earth, but detailed information on its distribution is entirely missing in some marine ecoregions, especially in the high latitudes of the Southern Hemisphere. Here, we present an algorithm based on a series of filter thresholds to detect giant kelp employing Sentinel-2 imagery. Given the overlap between the reflectances of giant kelp and intertidal gree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
78
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(91 citation statements)
references
References 62 publications
2
78
0
Order By: Relevance
“…Given that classification accuracy was highest in regions with reduced water surface tension, such as in a pool or a slow-moving river run, techniques from this study would also be well-suited for lake environments [19]. Additionally, the Random Trees classifier most easily identified large, homogenous patches of algae and macrophytes, and would similarly perform well with other large groups of macroalgae and submerged aquatic vegetation, such as kelp or seagrass [96][97][98]. Despite these applications, this method is not optimal for distinguishing multiple aquatic species, as RGB imagery is spectrally sparse.…”
Section: Uav Monitoring Of Benthic Primary Producersmentioning
confidence: 92%
“…Given that classification accuracy was highest in regions with reduced water surface tension, such as in a pool or a slow-moving river run, techniques from this study would also be well-suited for lake environments [19]. Additionally, the Random Trees classifier most easily identified large, homogenous patches of algae and macrophytes, and would similarly perform well with other large groups of macroalgae and submerged aquatic vegetation, such as kelp or seagrass [96][97][98]. Despite these applications, this method is not optimal for distinguishing multiple aquatic species, as RGB imagery is spectrally sparse.…”
Section: Uav Monitoring Of Benthic Primary Producersmentioning
confidence: 92%
“…Our stepwise approach to image classification is a unique hybrid of other methods of image classification, which generally focus on simple band ratios (e.g., Dierssen et al, 2019;Mora-Soto et al, 2020) or a supervised classifier to quantify bottom habitat (e.g., Traganos and Reinartz, 2018b;Poursanidis et al, 2019), but not both. The ratio approach was applied first to all pixels, and when the threshold was met, pixels were classified with no assumptions made on the other pixels (i.e., the one that did not meet the threshold criteria).…”
Section: Suitability Of Sentinel-2 For Benthic Habitat Mapping In Atlmentioning
confidence: 99%
“…The band ratios include vegetation indices based on red-edge indices such as NDVI and the Red-Green ratio, which can be effective tools for quantifying intertidal vegetation at low tide or vegetation that floats at, or near, the surface (e.g., Barillé et al, 2010;Dierssen et al, 2019;Mora-Soto et al, 2020). Following Dierssen et al (2019) we found that the Red-Green ratio could successfully classify bare sand at shallow to moderate depths, albeit at a slightly lower threshold value (<0.30 this study, <0.35 Dierssen et al, 2019).…”
Section: Suitability Of Sentinel-2 For Benthic Habitat Mapping In Atlmentioning
confidence: 99%
See 1 more Smart Citation
“…Although more typically used to monitor blooms in estuarine and coastal habitats ( Ulva spp. : Mora‐soto et al., 2020), satellite data are also useful in mapping kelp species that span the water column and were pioneered in the east Pacific ( M. pyrifera: Mora‐soto et al., 2020; Cavanaugh, Siegel, Kinlan, & Reed, 2010). Simms and Dubois (2010) created a method for submerged kelp beds in the northwestern Atlantic, which could potentially be used on the subtidal L. hyperborea forests in Ireland.…”
Section: Resilience and Monitoring Of Laminaria Hyperborea Communitiesmentioning
confidence: 99%